The rise and fall of median wealth in the U.S.: A birth-cohort story - Philipp Jäger; Philip Schacht (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
We use recently published long-run microdata (SCF+) to investigate generational wealth dynamics in the U.S. over the last seven decades. We document that the median wealth of people born in the first half of the 20th century increased from one ten-year birth cohort to the next. For people born in the second half of the century, median wealth successively declined from cohort to cohort while wealth inequality within birth cohorts increased markedly. A synthetic saving approach reveals that the trend reversal is mainly caused by changes in savings, which are a result of stagnating income levels and, importantly, declining saving rates. We find no evidence that shifts in wealth accumulation preferences, observable household characteristics or other demographic changes can explain our findings. – – Wir verwenden kürzlich veröffentlichte langfristige Mikrodaten (SCF+), um die Dynamik des Generationenvermögens in den USA über die letzten sieben Jahrzehnte zu untersuchen. Wir dokumentieren, dass Medianvermögen von Menschen die in der ersten Hälfte des 20ten Jahrhunderts geboren wurden von einer Zehnjahreskohorte zur Nächsten anstieg. Für die in der zweiten Hälfte des 20ten Jahrhunderts Geborenen ging das Medianvermögen von Kohorte zu Kohorte sukzessive zurück, während die Vermögensungleichheit innerhalb der Geburtskohorten deutlich zunahm. Eine synthetische Sparberechnung zeigt, dass die Trendumkehr vor allem auf Veränderungen in der Ersparnisbildung zurückzuführen ist, die in stagnierenden Einkommensniveaus und, vor allem, in sinkenden Sparquoten begründet liegt. Wir finden keine Hinweise darauf dass Verschiebungen in den Präferenzen für Vermögensbildung, beobachtbare Haushaltsmerkmale oder andere demografische Veränderungen unsere Ergebnisse erklären können.
Keywords: D14; D31; E21; J10; 330; Wealth inequality; cohorts; synthetic saving; United States